Pengaruh Budaya Organisasi dan Kompetensi Terhadap Efektifitas Kerja Karyawan Perusahaan Plastik di Surabaya - Dendi Apriliyanto Handika Putra; Budi Pratama, Rico; Yafie, Ach. Ali; Fitrih N, Latiefatul; Febrita Sarie, Rena (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The aim of this research is to determine the partial and simultaneous influence of organizational culture and competence on employee performance. This research uses quantitative research methods with data collection techniques through distributing questionnaires and supported by secondary data. The data analysis technique used uses SPSS software. The sample in this research were all production employees of plastic companies in Surabaya. The total sample was 94 respondents from plastic company employees in Surabaya. The results of this research show that organizational culture variables have a significant effect on employee performance. The competency variable has a significant effect on the performance of Plastic Company employees in the city of Surabaya. Work culture variables and competency variables together have a significant effect on the performance of Plastic Company employees in Surabaya.